Seeing business like a state: Firms and industries after the digital revolution. (November 2022) - Davis, Gerald F; DeWitt, Theodore
What we know about firms and industries in the United States has been fundamentally shaped by governmental responses to the Great Depression. Mandates for regular disclosures by public corporations and a system of industry categories created for surveys of establishments gave us a synoptic view of the economy that served us well for generations. They also molded the development of the fields of strategic management and organization theory. But the tools and frameworks that made sense in the 1930s are a poor fit with the enterprises we encounter today. Basic terms like firm, industry, size, performance, employee, and nationality are contested. The field of strategic organization may be the academic discipline best suited to helping us transition to a new way of making sense of the organization of the economy.